PENGARUH KUNJUNGAN WISATAWAN MANCANEGARA DAN PERJALANAN WISATAWAN NUSANTARA TERHADAP PENYERAPAN TENAGA KERJA SEKTOR PARIWISATA DI INDONESIA - Maulana, Addin (Ministry Of Tourism, 2016)
This is an associative research to identify the relation between two or more variables. The variables studied are international tourist visits, domestic tourist visits, and the tourism employment in Indonesia. The research used SPSS and normality test data analysis, classic assumption test, double linier regression, and hypothetical test. From the double linier regression formula then resulted that the constant value is 15.401. It means that if there is no amount of international and domestic tourist visit, then the number of employment in tourism sector is 15.401. If there is one added to the number of international tourist visit, then it will influence the number of employment of 2.086. If there is one added to the number of domestic tourist visit, then it will influence the number of employment of -0.096. If using the double linear regression method, it is better to use R square adjusted to 0.886 or 88.6%. This shows that the percentage of the influence of independent variables (the number of international and domestic tourist visit) able to explain as much as 88.6% of dependent variable (the number of employment in tourism sector). As for the 11.4% is influenced by other variables not explained in the research. Hence, it is important to conduct research related to other variables that also influence the tourism employment.